STRATEGI MASYARAKAT NELAYAN DALAM PEMENUHAN KEBUTUHAN SUBSISTENNYA DI DESA WISATA PASIR PUTIH DALEGAN GRESIK - Elanda, Yelly; Alie, Azizah (Universitas Wijaya Kusuma Surabaya, 2020)
This article will talk about the subsistence crisis and the strategies undertaken by the fishing community of Dalegan Village to get out of the subsistence zone. The results of previous research have explained the occurrence of socio-economic changes in the Dalegan village community due to the opening of white sand beach tourism. However, that study has not specifically examined the condition of the Dalegan village fishing community. This article attempts to describe the subsistence conditions experienced by fishermen and how the fishermen's strategies are to meet their subsistence needs. This study uses a qualitative method with a narrative approach through interviews with fishermen in Dalegan Village. The results showed that the fishing community experienced an economic increase due to the opening of the white sand tourism village of Dalegan. However, the fishing community is still experiencing a subsistence crisis. The difficult conditions faced by fishermen are unfavorable natural conditions, insufficient capital, low human resources and inadequate technology. The strategy undertaken by fishermen to get out of the subsistence zone is by borrowing money from cooperatives; asking for help from neighbors, relatives and bosses; children and wives also work and fishermen switch to work in other sectors.Keywords: Fishermen Community, Subsistence Crisis, Tourism Village, Fisherman Strategy